THE DOMINANT POSITION OF MARKETPLACES IN COOPERATION AGREEMENTS WITH MICRO AND SMALL ENTERPRISES (MSEs) REFERRED TO THE PRINCIPLE OF BALANCE - Yoga Murti, Ignaz Pradhana; Mulyati, Etty; Ratna Permata, Rika (Jurnal Poros Hukum Padjadjaran, 2023)
As one of the pillars supporting the economy in Indonesia, Micro and Small Enterprises (MSEs) are an instrument of economic development and equitable distribution of community welfare. MSEs have a very important role in moving the wheels of the national economy. Currently, MSEs in running their business cannot be separated from information technology facilities, one of which is through the marketplace. However, in the implementation of transactions through the marketplace, there are problems in terms of making agreements between the marketplace and MSEs where there is a dominant position of one of the parties. The research method used in this research is normative juridical by focusing on library law research. The results show that in electronic transactions there is an imbalance in the position between the marketplace and the seller, including MSEs, which causes the position of MSEs to be vulnerable and the position is not balanced. In the cooperation agreement, there are terms and conditions that force MSEs to agree to all agreements determined unilaterally by the marketplace. Therefore, the role of the government is needed to assist and protect MSEs so that they are not disadvantaged by certain parties and can play an optimal role in the national economy.